Coronary Artery Disease Risk Factors among Employees of Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Pokhrel, Sunita; Neupane, Pushpa (Nepalese Heart Journal, 2015)
Background and Aims: As employees spent most part of their time at the worksite, it provides a venue to address multiple individual risk factors and promote health. We aim to assess the prevalence of risk factors for coronary artery disease among the employees of Shahid Gangalal National Heart Centre, Kathmandu, Nepal. Methods: It was a prospective, single centre study conducted among randomly selected 129 (35.15%) out of 367 employees of our centre. All selected employees were subjected to detailed blood pressure, anthropometric and metabolic parameters measurement to identify risk factors. Results: Among the 129 participant 85(65.9%) were female and 44(34.1%) were male. Mean age was 25.8 years. Most of the patients 93(72%) were below the age of 40 years. Based upon BMI, 64(49.6%) were overweight, 20 (15.5%) were Obese, normal BMI was found in 38(29.9 %) where as underweight was found in 7(5.4%) employee. Based upon Central waist circumference Central waist obesity was common in female than male. Only 10(7.8%) of the employee were found to be hypertensive. Nineteen (14.7%) employee had RBS of ?125mg/dl. Conclusions: The high prevalence of risk factors of coronary artery disease is alarming. There should be the urgent and targeted interventions to prevent, treat and control non communicable diseases and their risk factors. Nepalese Heart Journal 2015;12(2):79-81